The role of neck adipose tissue in lymph node metastasis of head and neck cancer - Pan, Yiqi; Xu, Ying; Fan, Cui; Miao, Xiangwan; Shen, Yilin; Wang, Quan; Wu, Jichang; Hu, Haixia; Wang, Hao; Xiang, Mingliang; Ye, Bin (Frontiers in Oncology, 2024)
Previous studies indicated that adipose tissue significantly influences cancer invasion and lymphatic metastasis. However, the impact of neck adipose tissue (NAT) on lymph node metastasis associated with head and neck cancer remains ambiguous. Here, we systematically assess the classification and measurement criteria of NAT and evaluate the association of adipose tissue and cancer-associated adipocytes with head and neck cancer. We delve into the potential mechanisms by which NAT facilitate cervical lymph node metastasis in head and neck cancer, particularly through the secretion of adipokines such as leptin, adiponectin, and Interleukin-6. Our aim is to elucidate the role of NAT in the progression and metastasis of head and neck cancer, offering new insights into prevention and treatment.